Aspectos clínico-laboratoriais e epidemiologia molecular de ceratites por Fusarium spp. no estado do Ceará, Brasil - Milanez, Edlâny Pinho Romão (2023)
The fungus keratitis is an opportunistic corneal infection with a suppurative and often ulcerative appearance that can progress to total blindness or even loss of the eyeball. Due to nonspecific signs and symptoms and quick progression, fungus keratitis is difficult to diagnose. If inadequately treated, it can lead to significant visual decreasement and, in severe cases, to total blindness or even loss of the eyeball. The epidemiological distribution is strongly associated with the places where the disease occurs and varies widely throughout the world, even between different regions of the same country and in different groups of individuals. In this context, we investigated clinical and epidemiological characteristics of cases of Fusarium keratitis that occurred between October 2019 and March 2022 in patients from the state of Ceará – a region with a semi-arid tropical climate, characterized by high temperatures and a large number of rural workers exposed at ecosystems where the etiological agents are present. The etiology of the cases was investigated with in vivo confocal microscopy, corneal scraping for microscopy and culture, in addition to sequencing of the RPB2 and TEF1α genes for molecular identification. Additionally, a sensitivity test was performed for amphotericin B (AMB), natamycin (NAT) and voriconazole (VOR). Fungal etiology was identified in 22.12% (50/226) of keratitis cases during the period. Exceptionally, Fusarium spp. was responsible for 84.0% (42/50) of cases with positive cultures. Among the data obtained from the patients, it was found that the average age was 44.7 years and the largest number belonged to the age group between 41 and 60 years, with 74.0% (37/50) belonging to the male sex. Of the total number of patients analyzed, 26.0% claimed to have some underlying disease, such as arterial hypertension (12.0%) and diabetes (10.0%). Regarding treatment, Amphotericin B and ketoconazole were the most used antifungals in 78.0% and 46.0% of cases, respectively. Keratoplasty occurred in 48.0% of the cases (24/50). Sequencing results in 27 strains detected a predominance of species from the F. solani complex (FSSC) (14/27) in addition to the F. fujikuroi complex (FFSC) and F. dimerum (FDSC). AMB and VOR were the antifungals that showed the best in vitro activity against the isolated 28 Fusarium tested, with mic values ranging from 0.06 - 8 μg/ml and 0.06 - 4 μg/ml, respectively. Minimum Inhibitory Concentration values for NAT ranged from 0.125 - >128 μg/ml. The data show the importance of Fusarium in the etiology of keratitis in patients from northeastern Brazil. The present study reveals, for the first time, the profile of fungal sensitivity and molecular characterization of these isolated. The results obtained may contribute to the understanding of the epidemiology and treatment of the disease in our environment.